2019
DOI: 10.1186/s12870-019-2112-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the Dicer-like family in cotton and analysis of the DCL expression modulation in response to biotic stress in two contrasting commercial cultivars

Abstract: BackgroundDicer-like proteins (DCLs) are essential players in RNA-silencing mechanisms, acting in gene regulation via miRNAs and in antiviral protection in plants and have also been associated to other biotic and abiotic stresses. To the best of our knowledge, despite being identified in some crops, cotton DCLs haven’t been characterized until now. In this work, we characterized the DCLs of three cotton species and analyzed their expression profiles during biotic stress.ResultsAs main results, 11 DCLs in the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
2
11
0
Order By: Relevance
“…Concerning the role of Dicer proteins in plant defense, little is known about DCL2, except that it is involved in the processing of viral dsRNA. However, it has also been observed that the quantity of DCL2 transcripts increases at the local site of infection by the CLRDV (Cotton leafroll dwarf virus) in a resistant genotype cotton Gossypium hirsutum [82]. This is in agreement with our results were up-regulation of both PvA_DCL2a and Pv_DCL2b is observed in incompatible interaction with C. lindemuthianum.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the role of Dicer proteins in plant defense, little is known about DCL2, except that it is involved in the processing of viral dsRNA. However, it has also been observed that the quantity of DCL2 transcripts increases at the local site of infection by the CLRDV (Cotton leafroll dwarf virus) in a resistant genotype cotton Gossypium hirsutum [82]. This is in agreement with our results were up-regulation of both PvA_DCL2a and Pv_DCL2b is observed in incompatible interaction with C. lindemuthianum.…”
Section: Discussionsupporting
confidence: 93%
“…DCL2 is responsible for producing 22-nt siRNA, and DCL4 is related to the generation of trans-acting small interfering RNAs (ta-siRNAs) and 21-nt siRNAs [55]. DCL3 generates 24-nt siRNAs which participate in RdDM [56,57]. However, the functions of various DCLs in G. biloba still need to be studied.…”
Section: The Structure Of Dna Methylation Pathway Genesmentioning
confidence: 99%
“…Altered expression of DCL1 was observed in Fibermax (virus-susceptible) and Delta Opal (virusresistant) cotton plants after infection with Cotton leafroll dwarf virus (CLRDV). At 1 dpi, the susceptible cultivar Fibermax showed significantly lower expression of DCL1 compared to the virus-resistant cultivar Delta Opal, however, significantly higher expression of DCL1 was observed in the susceptible cultivar at 5 and 15 dpi compared to the resistant cultivar [35]. On the other hand, DCL1 showed no differential expression in leaves, flowers or cones of hop cultivar Celeia infected with hop latent viroid or citrus bark cracking viroid [28].…”
Section: Discussionmentioning
confidence: 83%